2018
DOI: 10.3389/fphar.2018.00879
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Treatments: An Account of Recent Industrial Developments

Abstract: The different drugs and medical devices, which are commercialized or under industrial development for glioblastoma treatment, are reviewed. Their different modes of action are analyzed with a distinction being made between the effects of radiation, the targeting of specific parts of glioma cells, and immunotherapy. Most of them are still at a too early stage of development to firmly conclude about their efficacy. Optune, which triggers antitumor activity by blocking the mitosis of glioma cells under the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 214 publications
(209 reference statements)
1
87
0
1
Order By: Relevance
“…Glioblastomas (GBs) are the most aggressive and vascularized primary brain tumors [2]. Despite multimodal therapy including surgical removal, radiation, and chemotherapy, GBs are essentially incurable [3,4]. The heterogeneity, infiltrative characteristics, presence of glioma stem cells, and function of blood-brain barrier have been appointed as the main causes of therapeutic resistance and malignant relapse [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioblastomas (GBs) are the most aggressive and vascularized primary brain tumors [2]. Despite multimodal therapy including surgical removal, radiation, and chemotherapy, GBs are essentially incurable [3,4]. The heterogeneity, infiltrative characteristics, presence of glioma stem cells, and function of blood-brain barrier have been appointed as the main causes of therapeutic resistance and malignant relapse [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite multimodal therapy including surgical removal, radiation, and chemotherapy, GBs are essentially incurable [3,4]. The heterogeneity, infiltrative characteristics, presence of glioma stem cells, and function of blood-brain barrier have been appointed as the main causes of therapeutic resistance and malignant relapse [3,4]. Furthermore, the lack of anti-tumor immune response due to an immunosuppressive TME also contributes to the treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on cancer patients have been performed to determine the specific tumor markers, suitable treatment, and medication guidelines (Alphandéry, ; Davis, ). These efforts have been made to develop advanced treatments that can effectively treat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma is one of the most aggressive and difficult to treat cancers. It is characterized by a life expectancy following diagnosis of only 12-18 months [1]. Standard treatments are ineffective for a number of reasons, such as the incapacity of surgery to remove all glioblastoma multiforme (GBM) tumor cells, notably the infiltrative ones, the difficulty for chemo-therapeutic drugs to reach the tumor, due to the blood brain barrier (BBB) that prevents them from diffusing towards the tumor, and the limitations of radiotherapy, which cannot easily eradicate radio-resistant GBM cells, notably stem cell ones.…”
Section: Introductionmentioning
confidence: 99%
“…A final consideration concerns apoptosis, a mechanism of cellular death that could be weakened among GBM tumor cells, possibly making these cells resistant to standard treatments [123]. With the help of nanoparticulate systems, it has been shown that apoptosis could be restored, for example by heating magnetic nanoparticles in the presence of GBM cancer cells under the application of an alternating magnetic field at mild temperatures of 40-50 • C [1,16,42].…”
mentioning
confidence: 99%